2022
DOI: 10.1097/hs9.0000000000000736
|View full text |Cite
|
Sign up to set email alerts
|

Budget Impact Analysis of CAR T-cell Therapy for Adult Patients With Relapsed or Refractory Diffuse Large B-cell Lymphoma in Germany

Abstract: The aim was to assess the incremental costs of chimeric antigen receptor (CAR) T-cell therapy (axicabtagene ciloleucel, tisagenlecleucel) compared with standard of care in adult patients with relapsed or refractory diffuse large B-cell lymphoma (r/r DLBCL) from the German third-party payer perspective. A budget impact model was established over a 6-year period. Estimation of the third-line population: partitioned survival model based on outcome data from peer-reviewed literature, a top-down approach based on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…With a variety of emerging interventions for transplant-ineligible R/R DLBCL, health economic evaluations from a healthcare payer's perspective are needed. 4,58 We found that the 2L EF is formed by BR and Tafa-L, illustrating an innovation shift provided by Tafa-L. Therefore, Tafa-L can be seen as the currently most cost-effective intervention in the 2L setting.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…With a variety of emerging interventions for transplant-ineligible R/R DLBCL, health economic evaluations from a healthcare payer's perspective are needed. 4,58 We found that the 2L EF is formed by BR and Tafa-L, illustrating an innovation shift provided by Tafa-L. Therefore, Tafa-L can be seen as the currently most cost-effective intervention in the 2L setting.…”
Section: Discussionmentioning
confidence: 78%
“…2 In addition, from 2001 to 2011, the number of new NHL cases increased by 16.9% for women and by 35.6% for men. 3,4 Using the anti-CD20 antibody rituximab alongside cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) as first-line treatment has improved survival rates of patients with DLBCL. 5 However, 30%-40% of patients experience relapse or become refractory (R/R).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations